Soft tissue angiofibroma with atypical features - Suzanna J. Logan; Mark A. Edgar; Anthony P. Martinez (Elsevier, 2020)
Soft tissue angiofibroma (STAF) is a benign fibrovascular neoplasm with a broad differential diagnosis including both benign and malignant tumors. This report expands the histologic spectrum of STAF with a case showing transition of conventional tumor morphology to distinct area of increased cellularity and cytologic atypia with diffuse, strong desmin expression, but absent myogenin and MYO-D1 expression. Mitotic figures were rare and necrosis was absent. These features have not previously been reported in STAF. A fusion was identified between AHRR and NCOA2 genes, which is a known, recurring feature of STAF. Sixteen months following resection with negative margins, there was no evidence of recurrence. Further reports of STAF showing similar findings with longer clinical follow-up are needed to determine the clinical significance of these results.